2018
DOI: 10.1534/genetics.118.300923
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Instability Promoted by Overexpression of Mismatch Repair Factors in Yeast: A Model for Understanding Cancer Progression

Abstract: Mismatch repair (MMR) proteins act in spellchecker roles to excise misincorporation errors that occur during DNA replication. Curiously, large-scale analyses of a variety of cancers showed that increased expression of MMR proteins often correlated with tumor aggressiveness, metastasis, and early recurrence. To better understand these observations, we used The Cancer Genome Atlas and Gene Expression across Normal and Tumor tissue databases to analyze MMR protein expression in cancers. We found that the MMR gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 85 publications
(110 reference statements)
4
33
0
Order By: Relevance
“…We found two distinct phenotypes upon MutS-overexpression i.e., mutation phenotype and cell elongation phenotype. In yeast, overexpression of the primary mismatch repair complex (Msh2-Msh6) is shown to be mutagenic and the phenotype is attributed to replication fork instability due to enhanced Msh6-PCNA interaction 51 . In E.coli , if MutS-overexpression mediated mutations were due to replication fork instability, in our ssDNA recombineering experiments, MutS-overexpression should have equally rejected either G/t or C/a mismatch generating ssDNA oligo.…”
Section: Discussionmentioning
confidence: 99%
“…We found two distinct phenotypes upon MutS-overexpression i.e., mutation phenotype and cell elongation phenotype. In yeast, overexpression of the primary mismatch repair complex (Msh2-Msh6) is shown to be mutagenic and the phenotype is attributed to replication fork instability due to enhanced Msh6-PCNA interaction 51 . In E.coli , if MutS-overexpression mediated mutations were due to replication fork instability, in our ssDNA recombineering experiments, MutS-overexpression should have equally rejected either G/t or C/a mismatch generating ssDNA oligo.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that cooverexpression of the Msh2 and Msh6 MMR proteins in wild-type strains increased the frequency of heteroduplex rejection in the inverted repeat assay by 3.5-fold, and hypothesized that this was due to the increased availability of functional MSH complexes acting in heteroduplex rejection (Chakraborty et al , 2018. Because both the sir2D mutation, and Msh2 and Msh6 cooverexpression increased rejection, we asked if the increased rejection seen in sir2D strains would rise to an even higher level in the presence of pEAM272 (2m, MSH2, MSH6 plasmid).…”
Section: Sir2 Cac1 and Rtt106 May Act In Similar Stepsmentioning
confidence: 97%
“…The mutations comprising the pol30-8 allele (R61A, D63A) were introduced into pEAA578 (POL30::KANMX) by Q5 site-directed mutagenesis (New England Biolabs, Beverly, MA) to create the single-step integrating vector pEAA633 (pol30-8::KANMX). Plasmids pRS426 (2m, URA3) (Christianson et al 1992) and pEAM272 (MSH2, MSH6, 2m, URA3) ( Chakraborty et al 2018) were used in the MSH overexpression experiments presented in Table 2.…”
Section: Yeast Strains and Plasmidsmentioning
confidence: 99%
“…Such an experiment tests if the increases in rejection seen in the two conditions reflect common or distinct regulatory steps. In wild-type strains bearing pEAM272 the Msh2-Msh6 complex is overexpressed by ~8-fold (Chakraborty, Dinh and Alani 2018). Wild-type strains containing pEAM272 display a 4.3-fold increase, compared to those containing the empty vector pRS426, in the rejection ratio, consistent with an increased concentration of Msh2-Msh6 resulting in improved rejection by increasing the likelihood of mismatch recognition in heteroduplex DNA (Table 2).…”
Section: Deletion Of the Sir2 Silencing Factor Increases Anti-recombimentioning
confidence: 93%